Scientific models in philosophy of science - Bailer-Jones, Daniela (University of Pittsburgh Press Digital Editions, 2009)
"Scientists have used models for hundreds of years as a means of describing phenomena and as a basis tor further analogy. In Scientific Models in Philosophy of Science, Daniela M. Bailer-Jones assembles an original and comprehensive philosophical analysis of how models have been used and interpreted in both historical and contemporary contexts." "Bailer-Jones delineates the many forms models can take (ranging from equations to animals; from physical objects to theoretical constructs). and how they are put to use. She examines early mechanical models employed by nineteenth-century physicists such as Kelvin and Maxwell, describes their roots in the mathematical principles of Newton and others. and compares them to contemporary mechanistic approaches. Bailer-Jones then views the use of analogy in the late nineteenth century as a way of understanding models and linking different branches of science. She reveals how analogies can also be models themselves or can help to create them."--Jacket